Особенности интраорганных сосудов и нервных структур пищевода обезьян в норме и патологии - Бурова, В.И. (Вестник зоологии, 1967)
The article deals with the data on morphology of vascular and nervous components of oesophagus of some low species of simians in a normal and pathological state. It is shown that the lymphatic vessels in a normal state are presented by capillaries which form a superficial narrow-loop net in mucous membrane and wide-loop net in submucous layer. During pathological processes in an organism (tuberculosis, pneumonia) the vascular system is subjected to reformation. A varication of vessels is observed, the loops of vessels become irregular, with protrusions of flask kind and blind excrescence on their walls; the nervous structures are subjected to reactive alterations. All the presented alterations can be treated as adaptive to hypoxia which is caused by disturbance of hemodynamics and intoxication of the organism.